Individual variation in resistance to Brachiaria decumbens toxicity in sheep - Salam Abdullah (2021)
The offspring of rams which had shown resistance to Brachiaria decumbens poisoning in earliar experiments exhibited variability in response when fed the grass. Three out of seven sheep showed no ill effects at all. Three out of seven sheep showed no ill effects at all. The affected individuals showed slight pathological changes in the liver with no signs of jaundice and neurological disorders even after 8 weeks of grazing on B. decumbens. These preliminary observations suggest that there may be a genetic factor producing resistance which have been transmitted by the sires to their offsprings.